Systematics, genetics, and biogeography of intertidal mites (Acari, Oribatida) from the Andaman Sea and Strait of Malacca. (4th September 2018) - Pfingstl, Tobias; Lienhard, Andrea; Shimano, Satoshi; Yasin, Zulfigar Bin; Shau‐Hwai, Aileen Tan; Jantarit, Sopark; Petcharad, Booppa
Abstract: This study demonstrates for the first time the presence of marine‐associated mites in the Andaman Sea and Strait of Malacca and reveals a relatively high diversity of these taxa with six species from two different families: Selenoribatidae and Fortuyniidae. Indopacifica, a new genus of Selenoribatidae, is described from Thailand and Malaysia, with two new species, Indopacifica pantai n. sp. and Indopacifica parva n. sp. The genus is characterized by the unique combination of following characters: lacking lamellar ridges, incomplete dorsosejugal suture, fourteen pairs of notogastral setae, and presence of epimeral foveae. A phylogenetic reconstruction based on 18S ribosomal RNA sequences clearly confirms the distinctness of the new genus Indopacifica and places it close to the genus Rhizophobates . The lack of molecular genetic data of possible relatives impedes a clear assessment, and hence, we emphasize the need for further combined approaches using morphological and molecular genetic sequence data. All species show wide distribution areas within this geographic region suggesting that these taxa are good dispersers despite their minute size and wingless body. Molecular genetic data demonstrate recent gene flow between far distant populations of I. pantai n. sp. from the coasts of Thailand and two islands of Malaysia and hence confirm this assumption. The seasonally changing surface currents within this geographic area may favor hydrochorous dispersal and hence genetic exchange. Nevertheless, morphometric data show a slight trend to morphological divergence among the studied populations, whereas this variation is suggested to be a result of genetic drift but also of habitat differences in one population of Alismobates pseudoreticulatus .